Firms as tax collectors - Pablo Garriga; Dario Tortarolo (Institute for Fiscal Studies (IFS), 2022)
We show that delegating tax collection to large firms can help build tax capacity in weak-enforcement settings. We exploit two reforms in Argentina that dramatically expanded and subsequently reduced turnover tax withholding by firms. Combining firm-to-firm data with regression discontinuity and difference-in-differences methods around revenue eligibility thresholds we find that: (i) large firms appointed as collection agents (CAs) are not affected, (ii) firms commercially linked to CAs self-report more sales by 5.8 percent in response to higher withholding, (iii) firms respond symmetrically to a decrease in withholding by reporting lower sales. Tax-collecting firms can thus boost compliance and tax revenue.
Keywords: 330; Taxation procedures; Companies; Tax morale; Tax revenue; Argentina; Developing countries; Besteuerungsverfahren; Unternehmen; Steuermoral; Steuereinnahmen; Argentinien; Entwicklungsländer